Factors Influencing University Dropout in Distance Learning: A Case Study - Núñez-Hernández, Corina (2023)
In the field of higher education in Ecuador, there is a phenomenon where students abandon the career, they were initially enrolled in. This research article aims to identify the determining factors that influence dropout, analyzing sociodemographic variables and economic, technological, institutional, and academic variables. The methodology used is action research built from educational practice. A survey was used to address several factors applied to 260 students of the second, fourth, and seventh levels of undergraduate study at a private institution. As a result, it was found that the most determining factor for a student to abandon their university career in the distance mode, with 72.31%, is the economic factor. Finally, it is concluded that students' permanence is affected mainly by socioeconomic aspects, which cause economic resources, illness, lack of time, and academic performance to be the most representative factors when deciding whether to remain or abandon a university career. This information increases the bibliography that deals with student behavior to search for alternatives to work on students' permanence.